THE DEVELOPMENT OF MULTIMEDIA COURSEWARE FOR MALAYSIAN’S SECONDARY SCHOOLS USING HYBRID PROBLEM BASED LEARNING APPROACH - Shahbodin, F. (2007)

(untitled)
This paper discusses the uses of the various education learning theories such as Constructivist approach, Contextual Approach and Problem Based Learning (PBL) approach in developing the multimedia courseware called C2HADAM for science learning. The evidence suggests that PBL is an instructional approach that offers the potential to help student develop understanding and lifelong learning skills. A common feature of problem-based learning is to provide students with a range of resources that assist them in solving the problems. This paper also attempts to explore and highlight the PBL principles and Constructivist elements, the role of Information and Communication Technology (ICT) especially Internet and multimedia technologies in creating a PBL courseware. This paper also aims to discuss the development cycle involved in developing the multimedia courseware namely: analysis, design, development, implementation and evaluation. This study is part of the author PhD progress work which aim to test the implementation of PBL approach at selected Secondary school in Malaysia. The multimedia courseware focus on Science subject for form 2 (topic Nutrition), Malaysia secondary school known as C2HADAM is created which integrate PBL features and characteristic. Finally, this paper also will outline some of the screen captured as examples taken from the C2HADAM courseware